Photoacoustic Microscopy Provides Early Prediction of Tissue Necrosis in Skin Avulsion Injuries - Zhang D; Yuan Y; Zhang H; Yi X; Xiao W; Yu A (Dove Medical Press, 2021)
Dong Zhang, Ying Yuan, Hao Zhang, Xinzeyu Yi, Weidong Xiao, Aixi Yu Department of Orthopedics Trauma and Microsurgery, Zhongnan Hospital of Wuhan University, Wuhan, People's Republic of ChinaCorrespondence: Aixi Yu; Weidong XiaoDepartment of Orthopedics Trauma and Microsurgery, Zhongnan Hospital of Wuhan University, Wuhan, People's Republic of ChinaTel +86-027-67813120; +86-18707182868Email yuaixi@whu.edu.cn; xiaoweidong@whu.edu.cnBackground: Skin avulsion injuries caused by high-energy traffic and machinery accidents are important topics in the field of repair and reconstruction. The injury generates a skin flap with uncertain vascular basis resulting in ischemic necrosis of the distal portion of the flap. Yet there is lack of reliable way for estimating the extent of blood supply in damaged tissue, which has limited the possibility of prompt surgical intervention. Recent studies have confirmed that photoacoustic microscopy imaging has a wide range of applications in the biomedical field owing to its good performance in angiography.Methods: In our study, we successfully surgically induced skin avulsion injury on mice hindlimbs. Then, we used this novel approach to image skin microcirculation and predict skin necrosis with impaired blood supply after injury in live mice.Results and Conclusion: All skin tissues in the avulsed hindlimb flap group show different levels of necrosis at the end of the observation period. The "dark zone" with impaired microcirculation in PAM images, which continuously extends over time, was seen as a prediction of necrosis of skin tissue and at 60 min after surgery was similar to the area of clinical necrosis on postoperative day 7. All these indicate that photoacoustic microscopy imaging is a feasible, precise, high-resolution, non-invasive technique for early prediction of necrosis in skin avulsion injury, providing a promising tool for surgeons to manage the injury.Keywords: skin avulsion injuries, photoacoustic microscope, monitoring microcirculation